PENINGKATAN PRODUKSI BAWANG MERAH PADA DESA BINAAN MELALUI INDIKATOR BISNIS TEKNOLOGI DI DESA SONGAN KECAMATAN KINTAMANI BANGLI - I Made Suarta; Ida Ayu Agung Ekasriadi; I Wayan Sudiarsa (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Songan B Village, Kintamani District, Bangli Regency, is a highland area with potential for horticultural agriculture, particularly shallots. However, local farmers face two main problems: high pest infestations (onion caterpillars, leaf miners, thrips, and groundworms) and post-harvest marketing constraints due to limited market access, promotional strategies, and product packaging. In response, the Indonesian PGRI Mahadewa University (Universitas PGRI Mahadewa Indonesia), through its Technology Business Incubator (IBT) program, is providing mentoring to the Giri Amerta I shallot farmer group. Community service activities were implemented using the Technology Business Indicator approach, which included outreach, training, application of appropriate technology, ongoing mentoring, evaluation, and sustainability planning. The program focused on three main aspects: environmentally friendly pest control using biopesticides, pest traps, and natural enemies; pest prevention through an integrated farming system; and increased marketing capacity through promotional strategies, branding, digital media utilization, and market networks. The results of the activities demonstrated increased knowledge and skills among farmers in cultivating high-yielding, environmentally friendly shallots, as well as a growing awareness of the importance of modern marketing strategies. Through collaboration between universities and the village community, this program is expected to increase shallot productivity and strengthen the competitiveness of farmers' products in Songan B Village.